Techno-economic analysis and dynamic operation of green hydrogen-integrated microgrid: An application study - Jordan, Isaac; Ahmed Mohamed, Ahmed Haidar; M.F.M., Sabri; M.O., Abdullah (Elsevier Ltd., 2025)
The shift to renewable energy sources requires systems that are not only environmentally sustainable but also cost-effective and reliable. Mitigating the inherent intermittency of renewable energy, optimally managing the hybrid energy storage, efficiently integrating the microgrid with the power grid, and maximizing the lifespan of system components are the significant challenges that need to be addressed. With this aim, the paper proposes an economic viability assessment framework with an optimized dynamic operation approach to determine the most stable, cost-effective, and environmentally sound system for a specific location and demand. The green integrated hybrid microgrid combines photovoltaic (PV) generation, battery storage, an electrolyzer, a hydrogen tank, and a fuel cell, tailored for deployment in remote areas with limited access to conventional infrastructure. The study’s control strategy focuses on managing energy flows between the renewable energy resources, battery, and hydrogen storage systems to maximize autonomy, considering real-time changes in weather conditions, load variations, and the state of charge of both the battery and hydrogen storage units. The core system’s components include the interlinking converter, which transfers power between AC and DC grids, and the decentralized droop control approach, which adjusts the converter’s output to ensure balanced and efficient power sharing, particularly during overload conditions. A cloud-based Internet of Things (IoT) platform has been employed, allowing continuous monitoring and data analysis of the green integrated microgrid to provide insights into the system's health and performance during the dynamic operation. The results presented in this paper confirmed that the proposed framework enabled the strategic use of energy storage, particularly hydrogen systems. The optimal operational control of green hydrogen-integrated microgrid can indeed mitigate voltage and frequency fluctuations caused by variable solar input, ensuring stable power delivery without reliance on the main grid or fossil fuel backups.